PERBEDAAN HASIL BEPLAJAR KONSTRUKSI BANGUNAN BERDASARKAN MEDIA GAMBAR DAN ALAT PERAGA SMK NEGERI 1 LINTAU BUO - 624-632 , Rezky Damsury (CIVED, 2015)
Abstract       This research is motivated by the lack of student learning outcomes in training  Building Construction . In this study applied learning using Props and image . The purpose of this study was to determine the learning outcomes of students who are taught using props and media images on training Building Construction class X TGB SMK Negeri 1 Lintau Buo.      This study includes a quasi-experimental study (Quasi - Experimental Research) with the study design Randomized Control group pretest - posttest design . The population in this study is 31 students of class X which consists of 15 students X TGB A and 16 students X TGB B. The samples used saturated sampling technique , where all members of the population is used as a sample . In this study a class X was selected as a TGB B Class Props and X TGB A as Class Media Images. The instrument used in this study is the initial test (pretest) and final test (posttest) in the form of an objective matter of 33 items that have tested the validity , reliability , difficulty index and different power problems. Data were analyzed using SPSS (Independent - Samples T Test) and t test (two average difference) by using the value of Gain Score (Difference in the pretest to posttest).      The results of this study indicate that the Class Props with an average score of pretest 50.18  and posttest 79.35, while the Class Media Images has an average score of pretest 51.31 and posttest 73.33. Can be seen there is an increase in the student learning outcomes in Class Props by 58 % and Class Media Images Figure 42.92 % . After that tested the hypothesis using SPSS acquired Sig ( 2 - tailed ) < 0.05 or 0.00 < 0.05 and t-test ( t = 4.143 > table = 2,045 ) . This means that the use of props have a significant influence on learning outcomes of students of class X Construction Skills Program Architecture Engineering SMK Lintau Buo. Keywords : Props, Learning Outcomes, Building Contruction